Hydrogel containing astaxanthin and application thereof in prevention of skin aging

By loading astaxanthin microparticles into silk fibroin microcarriers to form a hydrogel carrier, the stability and particle size distribution of the existing astaxanthin delivery system are solved, and efficient delivery and stable release of astaxanthin in the prevention of skin aging is achieved.

CN119679633APending Publication Date: 2025-03-25SHANGHAI DERMATOLOGY HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311233198.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing astaxanthin drug delivery system has poor stability, wide particle size distribution range, need for improved preparation methods and easy aggregation, resulting in low application efficiency in skin aging prevention.

Method used

Using a hydrogel carrier, astaxanthin microparticles are loaded into the silk fibroin microcarrier, and astaxanthin is encapsulated by PEG-PLA copolymer to form a uniform small molecule particle size, improving its stability and release uniformity.

Benefits of technology

Through this method, the stability and uniformity of astaxanthin are improved, which significantly slows down the natural and photoaging of the skin under ultraviolet irradiation, and improves its antioxidant effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119679633A_ABST
    Figure CN119679633A_ABST
Patent Text Reader

Abstract

The hydrogel comprises microparticles containing astaxanthin, the microparticles comprise a PEG-PLA (Polyethylene Glycol-Polylactic Acid) copolymer and astaxanthin, and the astaxanthin is coated with the PEG-PLA copolymer. The hydrogel disclosed by the invention is smeared on the epidermis of a tested animal, and after UVA ultraviolet radiation, the skin surface is not red and swollen, is slightly thickened but is not rough and dry, the skin elasticity is not obviously reduced, and the amount of wrinkles is small and small. Therefore, the hydrogel provided by the invention can be prepared into cosmetics (such as sunscreen gel) or mask medical instruments, and the occurrence of natural aging of the skin after the skin is illuminated can be obviously slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for delivering a biological material, in particular to a method for efficiently delivering DNA to auditory cells, as well as a delivery carrier and a preparation method. Background Art

[0002] The skin is located on the body surface. It is the first and easiest organ to show signs of aging. It is also an important target organ for studying aging. Skin aging not only affects appearance, but also has a close etiological relationship with the occurrence of skin diseases. Therefore, preventing and delaying skin aging has become one of the hot topics in life science research.

[0003] Changes in skin collagen content, water content, and enzyme activity lead to changes in skin aging, which are manifested as thinning, dryness, wrinkles, pigmentation, and delayed wound healing (Aging Clinical and Experimental Research. 2008; 20: 195-200). Skin aging is a gradual process, and its endogenous mechanism is very complex. Among them, the oxygen free radical theory and mitochondrial damage theory are the most representative endogenous mechanism theories related to aging that are currently widely accepted at home and abroad. Peroxidation free radicals are produced during the metabolism of substances in the body, which have extremely strong oxidizing ability. When the damage caused by free radicals accumulates beyond the body's repair ability, it will cause cell rupture and apoptosis, eventually leading to skin aging (Acta dermatovenerologica Alpina, Pannonica, et Adriatica. 2012; 21: 33-6, Free Radical Biology & Medicine. 2002; 33: 573-4). Oxidative stress in both cells and extracellular space of aged skin is initiated by reactive oxygen species (ROS) (Journal of Dermatological Science. 2010; 58: 85-90). Mitochondria produce ROS while providing energy to the body through oxidative metabolism. Excessive ROS causes oxidative damage to mitochondrial DNA (mtDNA), leading to mtDNA mutations, related protein synthesis disorders, affecting the integrity of the respiratory chain, causing insufficient cell energy supply, and thus leading to aging (Mechanisms of Ageing and Development. 2012; 133: 30-6, Science, 1999; 286: 774-9).

[0004] The most important environmental hazard to skin aging is ultraviolet (UV) radiation, which can induce common deletion mutations and exogenous skin aging. Therefore, taking measures to reduce or avoid UV radiation can prevent the occurrence of skin photoaging to some extent. Studies have found that UV causes aging mainly through two pathways: 1) direct absorption of incident light by cellular components leading to the formation of excited states and subsequent chemical reactions; 2) photosensitization mechanism, in which light is absorbed by endogenous or exogenous photosensitizers to produce excited triplet states. In the process of skin anti-aging, endogenous antioxidants can avoid damage from free radicals, and natural external antioxidants also have the effect of reducing free radical changes.

[0005] Astaxanthin (3,3'-dihydroxy-4,4'-diketo-β,β'-carotene, ATX) is mainly found in the epidermis of algae, yeast, crustaceans and fish

[13] . It is a keto-carotenoid with 13 conjugated double bonds. Due to its special molecular structure, astaxanthin can prevent oxidative stress damage through various pathways and has strong antioxidant properties. Astaxanthin's ability to quench singlet oxygen and capture free radicals is more than 10 times higher than that of β-carotene and more than 100 times higher than that of vitamin E. Astaxanthin's special molecular structure can terminate chain reactions by scavenging free radicals and ROS, and can pass through the phospholipid bilayer of the cell membrane to protect cells from lipid peroxidation; it can also enhance the body's antioxidant enzyme system to reduce the level of free radicals and ROS, thereby preventing oxidative stress damage through various pathways. Studies have found that astaxanthin can reduce oxidative stress damage by increasing the activity of superoxide dismutase (SOD) and glutathione peroxidase (GPX) in cells. In addition, astaxanthin reduced ROS levels, increased mitochondrial membrane potential, and inhibited H2O2-induced cell necrosis.

[0006] Astaxanthin is poorly soluble in water, it is easily degraded under conditions such as light (especially ultraviolet light) and high temperature, has poor stability in the outside world and the gastrointestinal tract, and has the defect of unclear targeting of system applications (Food Chemistry. 2017; 225: 23-30). By improving the drug delivery system of astaxanthin, the decomposition rate of astaxanthin in the external environment can be slowed down, and the anti-skin aging effect of astaxanthin can be improved. By applying astaxanthin liposomes to the skin of mice exposed to ultraviolet light, the pathological changes caused by light damage can be improved and collagen damage can be reduced. Astaxanthin is made into siliconized liposomes, and then the siliconized astaxanthin liposomes are applied to the skin. As astaxanthin is gradually released, its free radical scavenging activity gradually increases (Applied Surface Science. 2017; 424: 15-9). In addition, astaxanthin liposomes have the advantages of high biocompatibility and safety, and have certain targeting and sustained release, and have the potential to be applied to the food industry and drug systems. However, there are still some problems to be solved with liposomes, such as: a wide range of particle size distribution, the need to improve the preparation method, poor stability, and the tendency of liposomes to aggregate and unsaturated fatty acids in the lipid layer to oxidize as the storage time increases (Food Hydrocolloids. 2014; 38: 28-39). The number of applications is too frequent, which brings inconvenience to the application in real life, so it is necessary to develop a new drug delivery system. Summary of the invention

[0007] One object of the present invention is to provide a hydrogel, wherein microparticles containing astaxanthin are loaded in silk fibroin microcarriers, which is beneficial to the hydrophilic delivery of astaxanthin.

[0008] Another object of the present invention is to provide a hydrogel containing astaxanthin microparticles loaded in silk fibroin microcarriers to improve the stability of astaxanthin and prevent oxidation.

[0009] Another object of the present invention is to provide a hydrogel to improve the uniformity of the particle size of microparticles containing astaxanthin and to improve the release uniformity and stability of astaxanthin.

[0010] Another object of the present invention is to provide an application of a hydrogel containing astaxanthin in the preparation of cosmetics or medical devices for slowing down natural skin aging.

[0011] A fifth object of the present invention is to provide an application of a hydrogel containing astaxanthin in the preparation of cosmetics or medical devices for slowing down skin photoaging.

[0012] A hydrogel comprises astaxanthin-containing microparticles, wherein the microparticles comprise PEG-PLA copolymer and astaxanthin, the PEG-PLA copolymer is wrapped outside the astaxanthin, and the weight ratio of PEG-PLA to astaxanthin is 10:1.

[0013] The microparticles of the present invention use PEG-PLA, wherein the molecular weight of PEG is 5000 g / mol and the molecular weight of PLA is 45000 g / mol.

[0014] The particle size of the microparticles of the present invention is 140±5 nm as measured by DLS.

[0015] The hydrogels suitable for the present application include gelatin, GelMA, hyaluronic acid, chondroitin sulfate, methacrylic acid-modified chondroitin sulfate, agarose and PLGA-PEG-PLGA copolymer.

[0016] Silk fibroin (SILK) has unique properties in drug delivery systems: excellent mechanical strength and biocompatibility; the β-folding structure of silk fibroin molecules can effectively control the degradation rate of materials, thereby controlling the drug release rate. The level of β-folding content is related to the preparation and treatment of the solution, which can determine the material degradation rate and regulate the loading and release of drugs; silk fibroin molecules have good processability.

[0017] The pH of silk fibroin is about 4, and charged amino acids can adsorb drugs through electrostatic forces under physiological conditions. The gel delivery system of silk fibroin nanospheres can effectively control the release rate of dual drugs, with better biocompatibility and degradability.

[0018] Another hydrogel includes astaxanthin microparticles and silk fibroin, wherein the astaxanthin microparticles are loaded in the silk fibroin gel, and the weight ratio of silk fibroin to astaxanthin is 10:1. The microparticles include PEG-PLA and astaxanthin, and the weight ratio of PEG-PLA to astaxanthin is 10:1.

[0019] Another hydrogel comprises astaxanthin microparticles and silk fibroin, wherein the astaxanthin microparticles are loaded in the silk fibroin gel, and the weight ratio of silk fibroin to astaxanthin is 10:1. The microparticles comprise PEG-PLA and astaxanthin, and the weight ratio of PEG-PLA to astaxanthin is 30:3.

[0020] The hydrogel of the present invention firstly wraps astaxanthin with PEG-PLA to prepare microparticles, and then carries the microparticles on silk fibroin to prepare gel.

[0021] A specific implementation method for preparing astaxanthin-containing microparticles comprises:

[0022] PEG-PLA and ATX were dissolved in acetonitrile solution as the organic phase;

[0023] Dimyristoylphosphatidylcholine (DMPC) is dissolved in an ethanol solution (e.g., 4 v / v%) as the aqueous phase. The aqueous phase is preheated to 65°C ± 2°C, stirred (e.g., 900 rpm) until DMPC is completely dissolved, then the organic phase containing ATX is added, and stirring (e.g., 900 rpm) is continued for more than 2 minutes, then the stirring speed is reduced (e.g., 300 rpm), and stirred at room temperature overnight;

[0024] Afterwards, the solution stirred overnight was centrifuged at least once (for example: 10 kDa centrifugal concentrator at 4000 g, 40 min, 4° C.) to remove unencapsulated ATX and organic solvent, etc., to obtain microparticles containing ATX (denoted as: PEG-ATX).

[0025] The prepared PEG-ATX is added to the silk fibroin solution and stirred and mixed, and then heated, for example, incubated in an oven at 37° C. for 30 minutes to obtain a hydrogel.

[0026] The hydrogel of the present invention was applied to the epidermis of the test animals. After UVA ultraviolet irradiation, there was no redness or swelling on the skin surface. Although it was slightly thickened, it was not rough or dry. The skin elasticity did not decrease significantly, and the wrinkles were few and relatively fine.

[0027] The hydrogel of the present invention is made into cosmetics (such as sunscreen gel) or medical devices such as facial masks, which can significantly slow down the occurrence of natural aging of the skin after being exposed to light. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of preparing the hydrogel of the present invention;

[0029] Figure 2A This is the particle size distribution diagram of PEG-ATX measured by DLS;

[0030] Figure 2B The morphology of PEG-ATX nanoparticles under transmission electron microscopy (TEM);

[0031] Figure 3 are photos of mouse skin after UVA irradiation; A is a photo of the mouse skin in the blank control group, B is a photo of the mouse skin in the model control group, C is a photo of the mouse skin in the astaxanthin original drug group, D is a photo of the mouse skin in the low-dose silk-PEG-ATX hydrogel group, E is a photo of the mouse skin in the high-dose silk-PEG-ATX hydrogel group, F is a photo of the mouse skin in the empty silk-PEG hydrogel group, and G is a photo of the mouse skin in the silk fibroin group;

[0032] Figure 4The figures are the H&E staining results of the mouse back skin tissue after UVA irradiation; wherein A is the staining image of the mouse skin in the blank control group, B is the staining image of the mouse skin in the model control group, C is the staining image of the mouse skin in the astaxanthin original drug group, D is the staining image of the mouse skin in the low-dose silk-PEG-ATX hydrogel group, E is the staining image of the mouse skin in the high-dose silk-PEG-ATX hydrogel group, F is the staining image of the mouse skin in the empty silk-PEG hydrogel group, and G is the staining image of the mouse skin in the silk fibroin group;

[0033] Figure 5 The results of Masson staining of the mouse back skin tissue after UVA irradiation; A is the staining image of the mouse skin in the blank control group, B is the staining image of the mouse skin in the model control group, C is the staining image of the mouse skin in the astaxanthin original drug group, D is the staining image of the mouse skin in the low-dose silk-PEG-ATX hydrogel group, E is the staining image of the mouse skin in the high-dose silk-PEG-ATX hydrogel group, F is the staining image of the mouse skin in the empty silk-PEG hydrogel group, and G is the staining image of the mouse skin in the silk fibroin group;

[0034] Figure 6 The figures are the results of Weigert staining of the mouse back skin tissue after UVA irradiation; A is the staining image of the mouse skin in the blank control group, B is the staining image of the mouse skin in the model control group, C is the staining image of the mouse skin in the astaxanthin original drug group, D is the staining image of the mouse skin in the low-dose silk-PEG-ATX hydrogel group, E is the staining image of the mouse skin in the high-dose silk-PEG-ATX hydrogel group, F is the staining image of the mouse skin in the empty silk-PEG hydrogel group, and G is the staining image of the mouse skin in the silk fibroin group. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

[0036] Unless otherwise specified, all other reagents used in the examples of the present invention were purchased from Sigma-Aldrich.

[0037] Example 1 Preparation and characterization of hydrogel containing astaxanthin

[0038] The preparation process of the hydrogel in this embodiment is as follows Figure 1 As shown, it includes two processes: preparation of microparticles containing astaxanthin and preparation of hydrogel.

[0039] The method for preparing microparticles containing astaxanthin is as follows:

[0040] (1) 30 mg of PEG-PLA was dissolved in 1 ml of acetonitrile solution as the organic phase, and ATX (2 mg) was then dissolved therein;

[0041] (2) 3 mg of DMPC phospholipid was dissolved in 10 ml of 4 v / v% ethanol solution as the aqueous phase. The aqueous phase was preheated to 65 degrees and stirred at 900 rpm until DMPC was completely dissolved. The organic phase containing ATX was added dropwise within 3 min, and stirred at 900 rpm for 2 min. Then the stirring speed was adjusted to 300 rpm and stirred at room temperature overnight until the organic phase evaporated.

[0042] (3) A 10 kDa centrifugal concentrator (Millipore) was centrifuged at 4000 g for 40 min at 4°C to remove unencapsulated ATX and organic solvents. The tube was centrifuged twice to obtain about 500 μl of nanoparticles (denoted as PEG-ATX or PEG-ATX nanoparticles).

[0043] The method for preparing the hydrogel is as follows:

[0044] PEG-ATX nanoparticles were added to the silk fibroin solution (purchased from Suzhou Silkmate Biotechnology Co., Ltd.), stirred to evenly disperse it in the solution, and placed in an oven at 37°C for incubation for 30 minutes to form a hydrogel.

[0045] like Figure 2A As shown, the particle size of PEG-ATX measured by particle size analyzer (DLS) is 142.1±0.7789nm. Transmission electron microscopy (TEM) results show that PEG-ATX has a smooth surface and a spherical structure of roughly uniform size, with a particle size of about 60.73±12.33nm (see Figure 2B ).

[0046] Example 2 Evaluation of hydrogel against skin aging

[0047] Female SKH-1 mice aged 6-8 weeks were selected to establish a UV radiation photoaging model in mice. The mice were divided into the following categories:

[0048] (1) Blank control group;

[0049] (2) model control group;

[0050] (3) astaxanthin group;

[0051] (4) group embedded with low concentration (10 w / v%) silk-PEG-ATX hydrogel;

[0052] (5) group embedded with high concentration (50 w / v%) silk-PEG-ATX hydrogel;

[0053] (6) empty silk-PEG-silk fibroin hydrogel group;

[0054] (7) Silk protein group.

[0055] The corresponding preparations were applied to the mouse skin, and the changes in the mouse skin between different groups were observed.

[0056] 3.1 Evaluation of the mouse skin in each group after UVA irradiation

[0057] like Figure 3 As shown in the figure, after 70 days of regular UV irradiation, the skin of mice in each group showed corresponding changes; the mice in the blank control group had no pigmentation, no subcutaneous hemorrhage, slight wrinkles on the surface, and good elasticity ( Figure 3 A); After UV irradiation, the skin color of mice in the model control group turned red, uneven in color, with dilated capillaries, a small amount of erythema, rough and thickened skin surface, dryness, desquamation and leather-like appearance, loss of elasticity, and multiple obvious deep wrinkles ( Figure 3 B); The skin of mice in the original astaxanthin group was red and swollen, with a small number of bleeding spots, dry and thickened, slightly desquamated, reduced surface elasticity, and moderate wrinkles ( Figure 3 C); The skin of mice in the low-dose silk-PEG-ATX hydrogen group showed slight redness, no edema, slightly rough and thickened, slightly dry, slightly reduced elasticity, and mild wrinkles ( Figure 3 D); The skin surface of mice in the high-dose silk-PEG-ATX hydrogen group showed no redness or swelling, but slightly thickened, no roughness or dryness, slightly decreased elasticity, and a few fine wrinkles ( Figure 3 E); The skin surface of mice in the empty silk-PEG-silk fibroin hydrogel group and the silk fibroin group showed no redness or swelling, thickening, roughness and dryness, decreased elasticity, and moderate wrinkles ( Figure 3 F and Figure 3 G).

[0058] 3.2 H&E staining evaluation

[0059] Observation under H&E staining microscope showed that compared with the blank control group, the epidermis of mice in the model control group and astaxanthin original drug group was hyperplastic and hyperkeratotic, the epidermal ridges were flattened, the epidermal thickness increased significantly, which was higher than that of the other five groups, the dermal collagen fibers were loose, missing, broken, curled, loosely structured, and disordered, and the dermal inflammatory cells increased ( Figure 4 A. Figure 4 B and Figure 4 C); Compared with the blank control group, the epidermis of mice in the low-dose silk-PEG-ATX hydrogel group was slightly thickened, the dermal fibers were slightly loose and curled, and the inflammatory cells were slightly increased ( Figure 4 A and Figure 4 D); In the high-dose silk-PEG-ATX hydrogel group, the epidermal thickness of mice did not increase significantly, the dermal collagen fibers did not show obvious structural changes, and the inflammatory cells increased slightly ( Figure 4 E); The epidermis of mice in the empty silk-PEG-silk fibroin hydrogel group and the silk fibroin group was moderately thickened and hyperkeratotic, the dermal collagen fibers were loose, missing, broken, curled, loosely structured, and disordered, and the dermal inflammatory cells increased ( Figure 4 F and Figure 4 G).

[0060] 3.3Masson staining

[0061] Masson staining microscopy revealed that the dense collagen fibers of the blank control group were arranged in parallel and the collagen bundles were slender ( Figure 5 A). Compared with the blank control group, the epidermis and dermis of the mice in the model control group were significantly thickened, the collagen bundles were slender and arranged in disorder, and some collagen fibers were denatured and homogenized, presenting clumps ( Figure 5 B). Compared with the model control group, the original astaxanthin group ( Figure 5 C), empty silk-PEG hydrogel group ( Figure 5 D) The mice in the silk fibroin group showed no significant difference from the model group, with disordered collagen arrangement and denaturation; the collagen disorder of the mice in the low- and high-dose silk-PEG-ATX hydrogel groups was significantly reduced compared with the model control group, and the arrangement was more uniform ( Figure 5 E). The skin surface of mice in the empty silk-PEG-silk fibroin hydrogel group and the silk fibroin group showed no redness or swelling, thickening, roughness and dryness, decreased elasticity, and moderate wrinkles ( Figure 5 F and Figure 5 G).

[0062] 3.4 Weigert staining

[0063] The back skin of mice in each group was stained with Weigert staining. Figure 6 A. Figure 6 B. Figure 6 C. Figure 6 D. Figure 6 E. Figure 6 F and Figure 6 As shown in Figure 2G, microscopic observation revealed that the elastic fibers of the blank control group mice appeared as long and thin black fibers scattered among the collagen fibers. Compared with the blank control group mice, the elastic fibers of the model control group, astaxanthin original drug group, empty silk-PEG hydrogel group, and silk fibroin group mice increased significantly and became thicker, and some of the hyperplastic elastic fibers were broken and entangled. The elastic fibers of the low- and high-dose silk-PEG-ATX hydrogel groups increased and became thicker, but the number of elastic fibers was significantly lower than that of the model control group.

Claims

1. A hydrogel, characterized in that Containing astaxanthin microparticles, the microparticles include PEG-PLA copolymer and astaxanthin, the PEG-PLA copolymer is wrapped outside the astaxanthin, and the weight ratio of PEG-PLA:astaxanthin is 10:

1.

2. The hydrogel according to claim 1, characterized in that The particle size measured by DLS is: 140±5nm.

3. The hydrogel according to claim 1, characterized in that The ratio of PEG to PLA is 1:

9.

4. The hydrogel according to claim 1, characterized in that The molecular weight of the PEG is 5000 g / mol.

5. The hydrogel according to claim 1, characterized in that The molecular weight of the PLGA is 45000 g / mol.

6. The hydrogel according to claim 1, characterized in that The preparation method of the microparticles is as follows: PEG-PLA and ATX were dissolved in acetonitrile solution as the organic phase; DMPC is dissolved in ethanol solution as the aqueous phase. The aqueous phase is preheated to 65℃±2℃, stirred until DMPC is completely dissolved, and then the organic phase containing ATX is added and stirred for more than 2 minutes, then the stirring speed is reduced and stirred at room temperature overnight; Afterwards, the solution stirred overnight is centrifuged at least once to remove unencapsulated ATX and organic solvent, etc., to obtain microparticles containing ATX.

7. The hydrogel according to claim 1 or 6, characterized in that It also includes silk fibroin, and the astaxanthin-containing microparticles are loaded on the silk fibroin to form a hydrogel.

8. The hydrogel according to claim 7, characterized in that The amount of silk fibroin used is 10 times the weight of astaxanthin.

9. Use of the hydrogel according to claim 1 in preparing cosmetics or medical devices for slowing down natural skin aging.

10. A composition characterized in that The hydrogel according to any one of claims 1 to 8 is a cosmetic or a medical device.